Artificial Intelligence on Fashion and Textiles Proceedings of the Artificial Intelligence on Fashion and Textiles (AIFT) Conference 2018, Hong Kong, July 3-6, 2018 - Wong, Wai Keung; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book includes the Proceedings of the Artificial Intelligence on Fashion and Textile conference 2018 which provides state-of-the-art techniques and applications of AI in the fashion and textile industries. It is essential reading for scientists, researchers and R&D professionals working in the field of AI with applications in the fashion and textile industry; managers in the fashion and textile enterprises; and anyone with an interest in the applications of AI. Over the last two decades, with the great advancement of computer technology, academic research in artificial intelligence (AI) and its applications in fashion and textile supply chain has been becoming a very hot topic and has received greater attention from both academics and industrialists. A number of AI-related techniques has been successfully employed and proven to handle the problems including fashion sales forecasting, supply chain optimization, planning and scheduling, textile material defectdetection, fashion and textile image recognition, fashion image and style retrieval, human body modeling and fitting, etc.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence